Development of a psychological frailty index: results from the China health and retirement longitudinal study - Zhao, Jinlong; Liu, Justina Yat Wa; Fernández, Daniel; Tyrovolas, Stefanos (Frontiers in Psychology, 2025)
ObjectivePsychological frailty, an emerging concept, lacks a standardized definition, measuring instrument, and empirical evidence in Asian (especially Chinese) populations. An effective instrument to measure psychological frailty should be urgently developed. Therefore, this study aimed to develop and initially validate a Psychological Frailty Index (PFI) based on the China Health and Retirement Longitudinal Study (CHARLS). The study assessed the applicability of the PFI to adverse health outcomes as a secondary aim.ResultsFactor analysis of the 15-item PFI extracted four factors of psychological frailty (psychological distress, cognitive decline, physical vulnerability, and memory decline). The PFI demonstrated satisfactory internal consistency (Cronbach’s alpha = 0.764) and criterion validity (rho = 0.806). Psychological frailty was significantly associated with lower life expectancy (odds ratio [OR] 1.98, 95% confidence interval [CI] 1.71–2.29), higher outpatient treatments (1.25, 1.03–1.51), and increased hospitalization (1.45, 1.22–1.74).ConclusionThe PFI could be a reliable instrument for identifying psychological frailty. The PFI is a novel tool that measures health indicators of older adults at risk of increased psychological vulnerability, but it requires further validation.